Apakah Transfer Pricing Mempengaruhi Pajak? : Tinjauan Sistematis - Sulthan Yusuf Abdullah; Memen Kustiawan; Ida Farida Adi Prawira (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
Transfer Pricing become a problem in its application to some countries because it affects state revenue. Some companies apply Transfer pricing to avoid paying taxes. The purpose of this study is to aims does transfer pricing has an effect on the taxes paid by the company with the focus of the research answering the question